2018
DOI: 10.21873/anticanres.12612
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoAntitumor Effects of Pyrimethamine on Non-small Cell Lung Cancers

Abstract: PYR demonstrated anti-tumour effects on NSCLC in vitro and in vivo, indicating its therapeutic potential against human NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…After treatment with pyrimethamine, we observed that pyrimethamine significantly inhibited the growth of DX2-inducible A549 cells compared to EV-inducible A549 cells ( Figure 3 ). Pyrimethamine was reported to show the anti-tumor effect against cancer cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], but its mechanism was still veiled [ 19 ]. Our results showed that the increased level of DX2 leads the strong anti-tumor effect, suggesting that DX2 could be one of the targets for pyrimethamine-mediated anti-tumoral effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment with pyrimethamine, we observed that pyrimethamine significantly inhibited the growth of DX2-inducible A549 cells compared to EV-inducible A549 cells ( Figure 3 ). Pyrimethamine was reported to show the anti-tumor effect against cancer cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], but its mechanism was still veiled [ 19 ]. Our results showed that the increased level of DX2 leads the strong anti-tumor effect, suggesting that DX2 could be one of the targets for pyrimethamine-mediated anti-tumoral effect.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrimethamine was launched in 1953 for the treatment of malaria as a dihydrofolate reductase (DHFR) inhibitor ( ), and more recently for the treatment of toxoplasmosis combined with a sulfonamide [ 13 , 14 ]. Pyrimethamine also has been widely studied for the treatment of advanced solid tumors such as lung cancer, ovarian cancer, triple negative breast cancer, and chronic lymphocytic leukemia based on the various mechanisms including signal transducer and activator of transcription 3 (STAT3) inhibition [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], differently from DX2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat infections caused by protozoan parasites, such as Plasmodium falciparum and Toxoplasma gondii (Masur et al, 2000;Mockenhaupt et al, 2001;Hill and Dubey, 2002). In addition to its antimalarial effects, several studies have reported that pyrimethamine might be beneficial in the treatment of different types of tumors, including lung cancer (Lin et al, 2018), melanoma (Giammarioli et al, 2008;Tommasino et al, 2016), breast cancer (Khan et al, 2018), and acute myeloid leukemia (Sharma et al, 2016). It has been suggested that the mechanism underlying this activity involves the induction of cathepsin B-dependent and caspase-dependent apoptotic pathways, inhibition of STAT3, activation of the Caspase8/9, and cell cycle arrest in S-phase.…”
Section: Introductionmentioning
confidence: 99%
“…Pyr can also inhibit the STAT3 pathway in breast cancer cells (5). Pyr also has a broad range of effects in non-small cell lung cancers (6). However, the target of Pyr has not been elucidated before.…”
Section: Introductionmentioning
confidence: 99%